Unspeakable Histories : Film and the Experience of Catastrophe. - Guynn, William (Film and culture., 2016)
In Unspeakable Histories, William Guynn focuses on the sensation of encountering past events through film. Film is capable, he argues, of triggering moments of heightened awareness in which the barrier between the past and the present can fall and the reality of the past we thought lost can be momentarily rediscovered in its material being. In his readings of seven exceptional works depicting twentieth century atrocities, Guynn explores the emotional resonance that still adheres to traumatic historical events. Guynn considers dimensions of experience that historiography leaves untouched. Yaël.